2005
DOI: 10.1103/physreve.72.031510
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of amorphous solid water: Low-density, high-density, and very-high-density amorphous ices

Abstract: We describe the phase diagram of amorphous solid water by performing molecular dynamics simulations using the simple point charge (SPC/E) model. Our simulations follow different paths in the phase diagram: isothermal compression/decompression, isochoric cooling/heating and isobaric cooling/heating. We are able to identify low-density amorphous (LDA), highdensity amorphous (HDA), and very-high density amorphous (VHDA) ices.The density ρ of these glasses at different pressure P and temperature T agree well with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 62 publications
(152 reference statements)
4
45
0
2
Order By: Relevance
“…We find that hot compression produces significantly greater density at the same pressure than cold compression. Similar type of behavior has also been observed in case of amorphous water/ice (Loerting et al 2001;Giovambattista et al 2005). The reason for this is that the high-temperature liquid has access to a wider fraction of configuration space than the low temperature glass and is more readily able to accommodate its structure to high-pressure conditions.…”
Section: Discussionsupporting
confidence: 62%
“…We find that hot compression produces significantly greater density at the same pressure than cold compression. Similar type of behavior has also been observed in case of amorphous water/ice (Loerting et al 2001;Giovambattista et al 2005). The reason for this is that the high-temperature liquid has access to a wider fraction of configuration space than the low temperature glass and is more readily able to accommodate its structure to high-pressure conditions.…”
Section: Discussionsupporting
confidence: 62%
“…Gutierrez and Rogan [119] have simulated GeO 2 at 1500 K and 3000 K. At these temperatures, the system seems to be made of slightly distorted GeO 4 tetrahedra which are linked by corners and have a Ge − O − Ge angle of 130 o , similar to the experimental value in the amorphous phase (GeO 2 glass). A volume collapse, in the range 4 − 8 GP a, is seen from the pressure-volume curve and may be the signature of a liquid-liquid phase transition, in analogy with water [120]. Van Hoang has carried out a similar study [59] factor T (r) compared to experimental findings [57].…”
Section: Simulation Of Liquid and Amorphous Germaniamentioning
confidence: 99%
“…[10] Simulation studies suggest that VHDA ice should be considered as the amorphous solid counterpart to the high-density liquid water phase under ambient conditions, rather than HDA. [11,12] Koza et al [13] demonstrated, by using inelastic neutron scattering, that HDA and VHDA ice appear to be heterogeneous on the length scale of nanometers, and that different forms of HDA ice are obtained, depending on the exact preparation process. [13] By annealing HDA ice at normal pressure Tulk et al [14] observed a multitude of (metastable) amorphous ice states.…”
Section: Introductionmentioning
confidence: 98%